2016
DOI: 10.1002/aur.1660
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol and behavioral response to social evaluative threat in adolescents with autism spectrum disorder

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social behavior. One possible explanation for social communication deficits in ASD could be differences in biological systems that support responses to environmental stimuli. If so, it is unclear if differences in the arousal response to social stimuli in ASD are due to reduced interest in social information, or to an increased stress response. The hypothalamic pituitary adrenal axis facilitates arousal and the stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 93 publications
(105 reference statements)
2
35
0
Order By: Relevance
“…However, based on within-group analyses, distinct profiles emerged. Similar to previous findings using pairwise comparisons, children with ASD exhibited a blunted cortisol and RSA response, a finding consistently observed in other studies of children and adolescents with ASD (e.g.,(Edmiston et al, 2017; Lanni et al, 2012; Levine et al, 2012)). In contrast, the TD children showed an adaptive stress response and enhanced regulation when socially evaluated by others.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on within-group analyses, distinct profiles emerged. Similar to previous findings using pairwise comparisons, children with ASD exhibited a blunted cortisol and RSA response, a finding consistently observed in other studies of children and adolescents with ASD (e.g.,(Edmiston et al, 2017; Lanni et al, 2012; Levine et al, 2012)). In contrast, the TD children showed an adaptive stress response and enhanced regulation when socially evaluated by others.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the majority of research in individuals with ASD has explored the relationship between cortisol and psychopathology symptoms in relation to a stressor, rather than baseline levels. Edmiston, Blain, and Corbett [] have suggested that children with ASD may have limited insight into reporting their physiological arousal “in the moment,” though reporting on stable trait anxiety may be more reliable. Moreover, research in this area has predominantly focused on children and adolescents, with less literature focused on adults with ASD, and developmental effects seem likely.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many children with ASD have elevated cortisol in response to social interaction [Lopata, Volker, Putnam, Thomeer, & Nida, ; Corbett et al, ; Corbett, Schupp, & Lanni, ; Corbett, Schupp, Simon, Ryan, & Mendoza, ; Schupp, Simon, & Corbett, ]. During social evaluative threat, however, both children and adolescents with ASD show a maladaptive blunted cortisol response [Edmiston, Blain, & Corbett, ; Lanni, Schupp, Simon, & Corbett, ; Corbett et al, ; Levine et al, ; Jansen, Gispen‐de Wied, & Van der Gaag, 2000]. There is substantial evidence for elevated evening cortisol [Corbett, Schupp, Levine, & Mendoza, 2009; Corbett, Mendoza, Wegelin, Carmean, & Levine, ; Tomarken, Han, & Corbett, ], as well as lower morning values [Corbett et al, ; Corbett et al, ] in children with ASD.…”
Section: Introductionmentioning
confidence: 99%